Improving Phrase-Based Statistical Machine Translation with Rich Lexical Syntax - Hassan Awadalla, Hany; Sima'an, Khalil; Way, Andy (2005)
Until quite recently, extending Phrase-based Statistical Machine Translation (PBSMT) with syntactic structure caused system performance to deteriorate.